A Universal Polymerase Chain Reaction Developer. (16th December 2015) - Valentini, Paola; Pompa, Pier Paolo
Abstract: The versatility of PCR, the gold standard for amplification of DNA targets, is hampered by the laborious, multi‐step detection based on gel electrophoresis. We propose a one‐step, one‐tube method for the rapid (5 min) naked‐eye detection of PCR products, based on controlled aggregation of gold nanoparticles. Our method is universal, instrument‐free, and ultra‐sensitive, as it could detect as low as 0.01 zeptomoles of HIV template DNA in an excess of interfering human genomic DNA.